PROFIL PENDERITA KANKER SERVIKS DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR, BALI PERIODE JULI 2012 – JUNI 2013 - Winny Prabasari, Cokorda Istri (E-Jurnal Medika Udayana, 2017)
Cervical cancer is the most common gynecologic cancer in women and is the leading cause of death in developing countries. The high number of deaths may occur due to delay in treatment, because approximately 70% of cases come in an advanced stage condition. This study was conducted to determine the profile of patients with cervical cancer in Sanglah Hospital in Denpasar, Bali period July 2012 - June 2013. This study was a retrospective descriptive which is obtained from medical records of patients with cervical cancer who were treated in the period July 2012 - June 2013 at the Obstetrics and Gynecology Polyclinic and medical records Installation at Sanglah Hospital. Furthermore, the data such as profiles processed and presented in tables and graphics. Patients with cervical cancer by the age group 41-50 years had the largest number, which is 35 cases (39.3%). Most patients are parity of 3, which is 28 cases (31.5%), the number of patients recorded ever used oral contraceptives are 8 cases (9%). Histopathologic types most frequently encountered are the type of epidermoid which is 67 cases (75.3%), most of the cervical cancer patients come in stage III, which is 51 cases (57.3%). Cervical cancer is the highest case of gynecological malignancy in Sanglah Hospital with the most cases are in 41-50 years of age, parity of 3 children, with the most common histopathologic type of epidermoid, and the majority of patients come in stage III. Keywords : Cervical cancer, profile, age, parity, contraception, histopathology, staging